2020
DOI: 10.26710/jbsee.v6i2.1215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Process-Genre Approach on Writing Anxiety among English Academic Writing Learners in Pakistan

Abstract: Writing ability is a prerequisite to be successful in academic pursuits. Pakistani student writers experience a range of issues, including psychological, cognitive, social, and linguistic when they write. Writing instructors need to use appropriate teaching strategies and methodologies to tackle writing-related issues (Khan & Zaki, 2018). Most of the Pakistani ESL writing students are educated through the stereotypical teacher-centered Product Approach focuses on the memorization of ready-made answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…These results are consistent with results obtained from similar studies (e.g. Harpiansi, 2023, Saksono, 2022, Ajmal & Irfan, 2020.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with results obtained from similar studies (e.g. Harpiansi, 2023, Saksono, 2022, Ajmal & Irfan, 2020.…”
Section: Discussionsupporting
confidence: 93%
“…to write a text based on their learnt experiences. In this stage, certifying students" abilities to understand the features of a certain genre such as the communicative purpose, structure element of the text, grammatical patterns and relevant vocabulary usage, is so crucial (Hyland, 2007, Haryanti & Farnia, 2019, Ajmal & Irfan, 2020and Pham & Bui, 2021.…”
Section: Genre-based Approach (Gba)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, introducing academic writing to intermediate ESL learners poses challenges due to limited adoption and understanding of newer approaches such as Process and Genre. These conditions are not unique to the ESL/EFL contexts, as the English Language holds a significant role and position, particularly in academic settings (Ajmal, 2022;Getnet, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, beginner students encounter significant difficulties, including writing anxiety. A study by Siddique and Singh (2016) reveals that teaching practices related to writing skills, such as providing model texts and relevant vocabulary, have been identified as problematic at the pre-university level (Ajmal, 2022;Fareed, Jawed, & Awan, 2018). To address this issue and alleviate writing anxiety among ESL students, it is suggested that the product approach be gradually replaced by a more contemporary methodology called the combined process-genre approach (PGA), which is believed to be more beneficial and supportive.…”
Section: Introductionmentioning
confidence: 99%